Trends and Variations in Neonatal Length of In-hospital Stay in Canada - Wen, Shi Wu (Can J Public Health, 1998)
Purpose: To analyze spatio-temporal variations of neonatal length of in-hospital stay in Canada. Method: The length of in-hospital stay of 1,469,761 newborns in Canadian hospitals from April 1, 1984 to March 31, 1995 recorded by the Canadian Institute for Health Information was analyzed. Results: Neonatal length of in-hospital stay decreased from an average of 5.0 days in 1984 to 2.9 days in 1994. In 1994, the average neonatal length of in-hospital stay in Alberta was 2.5 days, which was 0.2 to 1.5 days shorter than other provinces. The spatio-temporal variations in neonatal length of in-hospital stay could not be explained by corresponding variations in birthweight and other neonatal disorders. Conclusions: Neonatal length of in-hospital stay has been substantially reduced in Canada in recent years but there remain important interprovincial variations. These variations are unlikely to be the results of changes or differences in patient-specific factors; policy played an important role.